Mining Operational Technical Study Pit Gaharu Blok 44-45 On Site Sambarata PT. Berau Coal - Malik; Amran (Journal of International Multidisciplinary Research, 2023)
PT Berau Coal as one of the National Coal mining companies operating in Berau Regency, East Kalimantan, is always trying to increase its coal production. PT Berau Coal's production target in 2014 is 23 million tons (Source: PT Berau Coal's 5-year long-term plan document). This increase in production can basically be achieved in 2 (two) ways, namely: 1. This is done by adding heavy equipment such as loading equipment and production transportation equipment so that production capacity becomes greater. 2. This is done by maximizing the productivity of mechanical equipment, namely existing loading and transport equipment. Increasing production capacity by maximizing the productivity of existing mechanical equipment is a relatively cheaper way than adding heavy equipment. Efficiency is the key to increasing the productivity of existing mechanical tools. Based on considerations of the company's need to increase production, one of which is by maximizing the productivity of existing mechanical equipment, this research aims to conduct a study on the productivity of PC1250 loading equipment and HD465 transportation equipment carried out at the Agaru Pit mining block 44-50 at the Samabarata site. PT Berau Coal so that the results of this study can determine the productivity of each mechanical device. The research method is carried out using direct computation, tabular method, and comparison between theoretical and actual and using the theory of calculation equations. Where the supporting data for analysis is in the form of field data as primary data and literature data as supporting (secondary) data. The results of this research study are the productivity of PC1250 loading equipment and HD465 transportation equipment where there are deviation values between actual and theoretical, both positive deviation (the optimum positive deviation between actual and theoretical is 97.3%) and negative deviation (optimum negative deviation between actual and theoretical is -11.8 %).